The Difference In The Results Of Urine Protein Levels In The Semi-Quantitative Method Of Esbach In Urine Accommodates 12 Hours With 24 Hours In Patients With Urinary Tract Infections - Septiawan, Dandi; Pauzi, Iswari; Tantontos, Erlin Yustin; Wiadnya, Ida Bagus Rai (Poltekkes Kemenkes Mataram, 2024)
Urinary tract infection is a common infection in the community caused by the growth of microorganisms in the human urinary tract, urinary tract infection is caused by bacteria by identifying the presence of protein in the urine Proteinuria (urine protein) is a protein found in urine that under normal circumstances does not get a high concentration in urine. Protein esbach gold method standard urine storage using urine storage 24 hours while in urine sampling can use urine storage 12 hours but quantitatively and scientifically there is no known difference in urine protein levels using the semi-quantitative esbach method. Determine the difference in protein content results measured by the semi-quantitative esbach method between urine samples collected for 12 hours and those collected for 24 hours in patients with urinary tract infections. This type of research is Observational Analytic with a cross sectional approach. The sample was in the form of urine in patients with urinary tract infections, the number of samples used a total sampling of 24 samples, the data taken were semi-quantitative urine protein levels of the esbach method. The collected data was then processed using SPSS with Mann Whitney test analysis. The average urine protein content of the 12-hour semi-quantitative method of esbach was 0.18 g / l, the average urine protein content of the 24-hour semi-quantitative method of esbach was 0.39 g / l, the difference in protein levels of the esbach method in urine collected 12 hours and 24 hours was 0.21 g / l, mathematically there was a difference while statistically there was no difference with the value of (p) = 0.748. 12-hour and 24-hour urine levels showed no difference in protein levels of semi-quantitative esbach method in patients with urinary tract infections.